Phytochemical analysis in economically important Ficus Benghalensis L. and Ficus Krishnae C.DC. using GC-MS - MAHIMA KARTHIKEYAN,; PARTHIBAN S,; SATHISHKUMAR RAMALINGAM, (International Journal of Pharma and Bio Sciences, 2019)
The plants of the Ficus family are divergent among the Angiosperms and are popular among botanists and plant biologists owing to their therapeutic and medicinal importance. Ficus benghalensis and Ficus krishnae were misidentified due to their similar phenotype and has been a major dispute due to their similar taxonomical features. These species are economically important and extensively used by ayurvedic physicians to treat dysentery, snake bite and skin diseases etc., The aim of this study is to identify and verify the presence of chemical constituents present in F.beghalensis and F.krishnae using Gas Chromatography-Mass Spectrometry (GC-MS) to differentiate the closely related plant species by chemical profiling. The leaves showed the presence of alkaloids, tannins and triterpenoids. These detected constituents proved to have various biological activities including anti-inflammatory, antioxidant, antiseborrheic, antieczemic and antiviral. Fourteen and twenty-one chemical compounds have been identified based on NIST and WILEY libraries respectively. The major constituents in F. benghalensis and F. krishnae are 1,3,4,5-Tetrahydroxy cyclohexane carboxylic acid with 37.56% and 21.71% respectively. The next major compounds found in F. benghalensis were 2-Hexadecen-1-ol (13.55%) and 14, 17-Octadecadienoic acid, methyl ester (11.44%) but in F. krishnae next major compound was Phytol (11.90%). To conclude, our findings suggests these 2 closely related species have contrasting chemical profiles. The plants of the Ficus family are divergent among the Angiosperms and are popular among botanists and plant biologists owing to their therapeutic and medicinal importance. Ficus benghalensis and Ficus krishnae are many times misidentified due to their similar phenotype and has been a major dispute due to their sharing taxonomical complexities. F. benghalensis and F. krishnae yet differ in their biological components that can be detected through analysis using Gas Chromatography-Mass Spectrometry (GC-MS). Hence, the aim of this study is to use methanolic leaf extracts of F. benghalensis and F. krishnae to identify the phytochemical constituents. The number of biologically active compounds detected through GC-MS analysis were 14 and 21, respectively for F. benghalensis and F. krishnae, where five of them were common in both the plant species but with varying peak areas indicating the distribution of phytochemical compounds between them. The phytochemical compounds were predicted for their biological activity based on the structure-activity relationship (SAR) analysis using online PASS (Prediction of activity spectra of substances) prediction tool. The detected compounds proved to have various biological activities including anti-inflammatory, antioxidant, antiseborrheic, antieczemic, antiviral, etc.